Association of eggs with dietary nutrient adequacy and cardiovascular risk factors in US adults. Issue 11 (5th March 2019) - Melough, Melissa M; Chung, Sang-Jin; Fernandez, Maria Luz; Chun, Ock K
Abstract: Objective: Whole eggs are rich sources of several micronutrients. However, it is not well known how egg consumption contributes to overall nutrient adequacy and how it may relate to CVD risk factors. Therefore, the present study aimed to determine how whole egg consumption contributes to nutrient intakes and to assess its association with CVD risk factors in US adults. Design: Cross-sectional study. Setting: The study was conducted using data from the National Health and Nutrition Examination Survey (NHANES) 2003–2012, a nationally representative survey of the US civilian population. Participants: Adults who completed two dietary recalls and provided information on relevant sociodemographic factors were included in the study ( n 21 845). Results: Approximately 73 % of adults were classified as whole egg consumers. Egg consumption was associated with greater intakes of protein, saturated fat, mono- and polyunsaturated fats, Fe, Zn, Ca, Se, choline, and several other vitamins and minerals. Egg consumption was associated with a higher likelihood of meeting or exceeding recommendations for several micronutrients. Egg intake was positively associated with dietary cholesterol consumption, but not with serum total cholesterol (TC) when adjusted for multiple potential confounders. In multiple linear regression analyses, TAG, TAG:HDL-cholesterol and TC:HDL-cholesterol were significantly lower with greater egg consumption. Egg consumption had no significant relationship with LDL-cholesterol or C-reactive protein, but was associated with higher BMI and waist circumference. Conclusions: Whole eggs are important dietary contributors of many nutrients and had either beneficial or non-significant associations with most CVD risk biomarkers examined.